Successful treatment of fulminant myocarditis with intra-aortic balloon pump counterpulsation combined with immunoglobulin and glucocorticoid in a young male adult - Li, Huanhuan; Li, Lun (Frontiers in Cardiovascular Medicine, 2022)
Background Fulminant myocarditis (FM) is a serious non-specific inflammatory disease of the myocardium. FM tends to occur in adolescents and the course of the disease progresses rapidly. It is prone to cardiogenic shock (CGS) and multiple organ failure (MOF) with high mortality. We report a case of FM with CGS and MOF in a young male who was successfully treated with intra-aortic balloon pump counterpulsation (IABP) combined with intravenous immunoglobulin (IVIG) and glucocorticoid (GC). Case summary A 21-year-old previously healthy man presented with fever, headache, and chest tightness. He came to the hospital for emergency treatment. The laboratory data showed that the levels of serum cardiac troponin I (cTnI), N-terminal B-type natriuretic peptide (NT-proBNP), myocardial zymogram, and neutrophils increased. Echocardiography showed pericardial effusion and decreased left ventricular systolic function. ECG showed diffuse ST-segment elevation. He was clinically diagnosed with FM and admitted to the intensive care unit for treatment. Within 48 h of admission, the clinical course of the patient deteriorated rapidly, with CGS accompanied by MOF, high atrioventricular block (AVB), and ventricular tachycardia (VT). After using mechanical circulatory support (MCS) therapy with IABP, IVIG, GC, continuous renal replacement therapy (CRRT), and mechanical ventilation complicated with a temporary cardiac pacemaker, he recovered normal cardiac function. He made a full recovery and was discharged home on day 21. Discussion For patients with FM, early diagnosis, close monitoring, timely use of MCS devices, and active comprehensive treatment are very important. MCS devices such as IABP can become lifesaving tools for the treatment of FM.